THE INFLUENCE OF SOCIAL AND CULTURAL NORMS ON THE UTILIZATION OF PUBLIC HEALTH SERVICES AT THE KALAR HEALTH CENTER – SOUTH ARU KALARKECAMATAN ARU ISLANDS REGENCY - Benamen, Mohamad Nurdin; HSudiyanto, Henry; Alamudi, M. Yusuf; Diana, Sulis (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
K3 maintains the safety of nurses in every health service facility to carry out their performance and maintain the safety of recipients or users of health services. Purpose of the study: to determine the effect of the implementation of SMK3 on the performance of nurses in the operating room of Sidowaras Hospital, Mojokerto Regency. This study uses a quantitative method using an analytical observational research design with a cross-sectional approach.. PopulationIn this study, all employees of the Sidwaras Hospital operating room, totaling 45 nurses, were involved and a sample of 35 respondents was obtained.Questionnaire data collection technique. Kthen tested using the Chi-Square Test and Logistic Regression Test. Results :The results of the study show that 0.005 <0.05 means that there is an influence between occupational health and performance. And 031 <0.05 means that there is an influence between occupational safety and performance. Occupational safety has a sig wald value of 0.955> 0.05 which means that occupational safety does not provide a significant partial influence on performance. Occupational health has a sig Wald value of 0.031> 0.05 which means that occupational health does not provide a significant partial influence on performance. Conclusion and suggestions:Hospitals are expected to continue to pay attention to and improve the implementation of the occupational safety management system. They need to provide facilities and infrastructure for occupational safety in each work unit, especially operating rooms, to reduce the risk of work accidents.